It's Better to Get It from Eastman! - Eastman Kodak Company (1956)
Front and back of an illustrated color postcard advertising the products and services of the Eastman Organic Chemicals Department (Division of the Eastman Kodak Company). The postcard features a humorous depiction of a harried-looking man attempting to brew his own chemicals on a rooftop. Postmarked from Rochester, New York, the postcard also includes a brief summary of Eastman’s available stock of chemical compounds as they pertain to the “chemical businessman.”
Keywords: Advertising; Advertising, Industrial; Chemical industry; Eastman Kodak Company; Commercial art